Male/Female Differences in Neuroprotection and Neuromodulation of Brain Dopamine - Bourque, Mélanie; Dluzen, Dean E.; Di Paolo, Thérèse (Frontiers in Endocrinology, 2011)
The existence of a sex difference in Parkinson’s disease (PD) is observed as related to several variables, including susceptibility of the disease, age at onset, and symptoms. These differences between men and women represent a significant characteristic of PD, which suggest that estrogens may exert beneficial effects against the development and the progression of the disease. This paper reviews the neuroprotective and neuromodulator effects of 17β-estradiol and progesterone as compared to androgens in the nigrostriatal dopaminergic (NSDA) system of both female and male rodents. The 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mice model of PD and methamphetamine toxicity faithfully reproduce the sex differences of PD in that endogenous estrogen levels appear to influence the vulnerability to toxins targeting the NSDA system. Exogenous 17β-estradiol and/or progesterone treatments show neuroprotective properties against NSDA toxins while androgens fail to induce any beneficial effect. Sex steroid treatments show male and female differences in their neuroprotective action against methamphetamine toxicity. NSDA structure and function, as well as the distribution of estrogen receptors, show sex differences and may influence the susceptibility to the toxins and the response to sex steroids. Genomic and non-genomic actions of 17β-estradiol converge to promote survival factors and the presence of both estrogen receptors α and β are critical to 17β-estradiol neuroprotective action against MPTP toxicity.